Intuitive eating in Greek-Cypriot adults: Influence of gender and body mass - Argyrides, Marios; Anastasiades, Elly (Frontiers in Psychology, 2022)
To date, research on eating behaviors has largely taken a pathological approach. More recently, researchers are increasingly taking a positive approach to explore adaptive eating styles. One such style that has recently received much research attention is intuitive eating. Recent work examining intuitive eating and its relationships with body mass and gender has yielded mixed findings. Here, we explored the differential effects of gender and body mass on intuitive eating scores in a sample of Greek-Cypriot adults. A total of 1312 adult participants (women n = 655; Mage = 34.49) completed the Intuitive Eating Scale-2 and provided demographic information. Our analyses revealed that men reported significantly higher intuitive eating scores than women. Body mass was significantly inversely associated with intuitive eating in both men and women. Additionally, a multivariate analysis of variance (MANOVA) indicated significant interaction effects between gender and body mass on intuitive eating were observed. These interaction effects were explored for each of the four subscales of intuitive eating, identifying differential associations for intuitive eating and BMI between men and women.